2002
DOI: 10.3354/meps228165
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of juvenile penaeid prawns in mangrove forests in a tropical Australian estuary, with particular reference to Penaeus merguiensis

Abstract: Several species of prawns, including juveniles of Penaeus merguiensis, will move into mangrove forests when the forests are inundated by flood tides. However, we do not know how extensively the prawns use the forests or whether some parts of the forests are more valuable to the prawns than others. We assessed the distribution of juvenile prawns in 3 different mangrove communities in intertidal forests adjacent to a small creek and a river in northern Australia between December 1993 and February 1995. The 3 man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Mangroves have generally been treated as a single habitat unit, the value of which has been inferred from samples taken at 1 stratum (or zone), usually along the seaward edge (Hindell & Jenkins 2004), but fish and invertebrate assemblages may vary strongly with distance into mangrove forests. Fish abundances and biomass may be greater at 'inland' mangrove positions (Ronnback et al 1999), with juvenile fish and prawns moving considerable distances into mangrove forests (Vance et al 1996), depending on topography and current patterns (Vance et al 2002). Conversely, assemblages of epibenthic nekton may be more abundant and diverse along the edge than inner forest regions of mangroves (Vance et al 1996, Meager et al 2003.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…Mangroves have generally been treated as a single habitat unit, the value of which has been inferred from samples taken at 1 stratum (or zone), usually along the seaward edge (Hindell & Jenkins 2004), but fish and invertebrate assemblages may vary strongly with distance into mangrove forests. Fish abundances and biomass may be greater at 'inland' mangrove positions (Ronnback et al 1999), with juvenile fish and prawns moving considerable distances into mangrove forests (Vance et al 1996), depending on topography and current patterns (Vance et al 2002). Conversely, assemblages of epibenthic nekton may be more abundant and diverse along the edge than inner forest regions of mangroves (Vance et al 1996, Meager et al 2003.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Fish abundance differed little between forest and edge, but species richness and biomass were lower in forest than along the edge. Recent work by Vance et al (2002) shows that differences in faunal abundances among regions within mangrove forests largely depend on local topography and water currents. In our study, water depth within a zone was a poor predictor of fish abundance, species richness, or biomass among sampling occasions.…”
Section: Zonation Of Fish Assemblages In Mangrovesmentioning
confidence: 99%
“…There is good information on the blue crab in Cheasapeake Bay, USA (EPIFANIO & GARVINE, 2001) and shrimps in Carpentaria Gulf, Australia (VANCE et al, 1990(VANCE et al, , 1998(VANCE et al, , 2002. Decapod larval ecology studies are scarce in Brazil and a proportion of these studies remain as unpublished thesis and monographs of limited availability.…”
mentioning
confidence: 99%
“…Water depth and sediment type, among others, were the factors most responsible for differences in shrimp abundances between habitats. However, water currents, as suggested by Vance et al (2002), Loneragan et al (1998) and Dall et al (1990) may also have an important influence on shrimp abundance.…”
Section: Discussionmentioning
confidence: 98%
“…Smaller shrimps are expected to be less active swimmers than bigger shrimps, therefore may be a tendency for net transport to the mangrove edges and mud flats (Vance et al, 2002;Rönnbäck et al, 2002;Loneragan et al, 1998). Data collected during 14 months near the mangrove forest (sand flat habitat) at Saco da Inhaca, also found that sizes smaller than 3 mm CL dominated the catches (Macia, unpublished data).…”
Section: Size Distributionmentioning
confidence: 93%